Retire often : how anyone can take multiple career breaks to unlock adventure, advance their career, and find financial freedom - Johnsrud, Jillian (Harriman House, 2025)
This book presents an approach to work-life balance centered on taking intentional career breaks, or "mini-retirements," throughout one's life. Drawing on the author's personal experiences and her work coaching others, it outlines strategies for planning and financing these breaks, managing career impacts, and aligning time away from work with personal priorities such as family, health, and long-term goals. The book includes practical guidance, examples, and exercises aimed at helping readers integrate periodic rest and reflection into their professional and personal lives.